The Mechanical And Durability Performance Of Woven Fiberglass Mesh Reinforced Lightweight Foamed Concrete - Serudin, Anisah Mat (2020)
Lightweight foamed concrete (LFC) is well known as a low-density concrete with a wide range of applications. However, since its weight is almost half that of conventional concrete, its strength can also be expected to be lower than that of normal concrete. Thus, short fibres (synthetic and natural fibres) were used by previous researchers to improve the performance of LFC. Even though there were improvements in its mechanical properties, yet these had a negative impact on its durability in the long term due to the deterioration of the fibres. Recently, the use of textile fabrics as a reinforcing element has gained considerable attention. Thus, the aim of this research was to perform an experimental investigation to establish the durability and mechanical performance of woven fibreglass mesh reinforced LFC. In this research, LFC samples were designed with densities of 600 kg/m3, 1100 kg/m3, and 1600 kg/m3 with a constant cement-to-sand ratio of 1:1.5, and cement-to-water ratio of 0.45. The textile fabric selected for this research was woven fiberglass mesh with different weights per area of 110, 130, 145, and 160 g/m2. The number of layer(s) for the observed confinement was detailed down to its effect on the performance of the LFC. As a result, reinforcement with woven fiberglass mesh enhanced the mechanical and durability performance of LFC. Moreover, through observations of the failure modes based on the mechanical tests, the unreinforced LFC showed a brittle behaviour, while the reinforced LFC showed a ductile performance, where the confinement with woven fiberglass mesh prevented sudden failure and delayed the propagation of cracks in the LFC under axial, bending, and tension loading.